Tailoring career education and counseling for Portuguese foster-youth - Silva, Ana Daniela (2011)
Young people living in out-of-homes care usually do not benefit from a gradual transition to adulthood, and without a stable family network to support this process, they mostly face, on their own, the changes related to an independent care from other adults ([1]). In Portugal, a considerable number of young people enter adulthood in an institutional context, leaving at that stage the foster care institutions, due to legal requirements ([2]; [3]). When these young people leave care, employment is necessary to replace the financial assistance assured by the welfare system until that moment. However, foster youth are at a higher risk of unemployment due to the fact that they are more likely, compared to their peers who live in stable family settings, to be involved in the criminal justice system, have lower academic skills and achievement rates, and present psychological and physical health problems. In this sense, these young people will highly benefit of tailored career education and development programs. This paper presents an analysis of foster youth career development and counseling needs in the context of the Portuguese educational system and labor market, and discusses implications for career counseling and educational interventions for this at-risk group of young people.